Electrochemically mediated CO₂ capture by polyaniline-graphene oxide nanocomposites - Brainard, Lauren, author; Peebles, Christie, advisor; Parada, German, committee member (Colorado State University. Libraries, 2025)
Rising atmospheric CO2 concentrations have driven demand for effective carbon capture technologies, particularly solutions compatible with existing industrial infrastructure. This study investigates electrochemical CO2 capture using polyaniline-graphene oxide (PANI-GO) nanocomposites as an alternative to traditional packed bed adsorption (PBA) methods. Building upon previous work with pressure swing adsorption (PSA) regeneration, this research explores voltage-swing mechanisms that enable both capture and regeneration through simple electrical input. PANI-GO was synthesized directly onto carbon cloth cathodes and assembled into electrochemical cells with NaCl electrolyte. Capture performance was evaluated by measuring effluent CO2 concentrations during voltage application (0.5-1V) and comparing results to conventional PBA systems. Statistical analysis revealed that electrochemical capture achieved significantly higher CO2 removal (mean: 203 ppm reduction) compared to PBA methods (mean: 87 ppm reduction, p = 0.00058). The electrochemical approach offers advantages in energy efficiency and regeneration simplicity, requiring only voltage removal to release captured CO2. While challenges remain regarding cell sealing, coating uniformity, and electrolyte optimization, these results demonstrate the viability of electrochemical carbon capture as a modular, low-energy solution for industrial emissions reduction. Future work will focus on scaling the technology, optimizing electrolyte composition with bicarbonate/carbonate solutions, and analyzing captured gas purity through chromatography.
Keywords: carbon capture; nanocomposite; chemical engineering; polyaniline; braphene oxide